2005
DOI: 10.1042/ba20030219
|View full text |Cite
|
Sign up to set email alerts
|

Biological effect of irradiated chitosan on plants in vitro

Abstract: For degradation of chitosan, chitosan with an 80% degree of deacetylation and a weight-average molecular mass (Mw) of approx. 48 kDa was irradiated with gamma-rays at doses up to 200 kGy in a 10% (w/v) solution. The Mw of chitosan was reduced from 48 to 9.1 kDa by irradiation. The characteristics of irradiated chitosan were analysed by using Fourier-transform IR spectroscopy and an elemental analyser. The amino group was found to be stable, whereas the C-O-C group decreased with increase in the dose. The produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…It is used in plant production as a growth biostimulator [ 6 ] and elicitor of pathogen resistance [ 7 , 8 ]. The biological activity of chitosan depends on diverse factors as its morphological structure, degree of deacetylation and molecular weight [ 9 , 10 ]. Chitooligosaccharides (COS) are high molecular weight homo- or heterooligomers obtained from chitin or chitosan [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is used in plant production as a growth biostimulator [ 6 ] and elicitor of pathogen resistance [ 7 , 8 ]. The biological activity of chitosan depends on diverse factors as its morphological structure, degree of deacetylation and molecular weight [ 9 , 10 ]. Chitooligosaccharides (COS) are high molecular weight homo- or heterooligomers obtained from chitin or chitosan [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that chitosan accelerated and prompted the plant's growth and morphological characteristics of various plants such as gerbera 6 (Wanichpongpan et al, 2000), soybean sprouts , and sweet basil . Luan et al (2005) demonstrated the stimulating effect of chitosan on shoot lengths and fresh biomass in several plants such as Chrysanthemum morifolium, Limonium latifolium, Eustoma grandiflora, and Fragaria ananasa. The research conducted by Salachna and Zawadzińska (2014) has shown that chitosan can be used as a biostimulator on freesia plants.…”
Section: Resultsmentioning
confidence: 97%
“…Gamma irradiation has been proposed as a useful method for the degradation of natural polysaccharides (cellulose, alginate, chitosan, etc.) via the cleaving of glycosidic bonds of polymer molecules [32,33,34]. The main advantages of radiation degradation for natural polysaccharides include the ability to forego chemicals or special conditions, ease of process control and large-scale application, a simple process, high degradation yield, high purity product, and low cost [32].…”
Section: Introductionmentioning
confidence: 99%